Antibacterial Drug Development: A New Approach Is Needed for the Field to Survive and Thrive - M. Courtney Safir; Sujata M. Bhavnani; Christine M. Slover; Paul G. Ambrose; Christopher M. Rubino (MDPI AG, 2020)
It is often said that the marketplace for new antibiotics is broken. This notion is supported by the observation that many recently-approved antibiotics to treat drug-resistant bacteria have failed commercially in a spectacular fashion. Today, companies with peak market-cap values in excess of USD 500 million to 1 billion prior to product launch regularly sell for pennies on the dollar a few years after market introduction. It is possible, however, that the market is not as broken as we perceive. That is, in the collective mind of the clinician, recently-approved antibiotics may be too-poorly differentiated to justify their broad use and inordinate cost relative to those already existing. Perhaps we in the antibacterial drug development field must change our way of thinking if we are to survive and thrive. Rather than reflexively developing new β-lactam-β-lactamase inhibitor combinations for every new enzyme that evades our current inhibitors, we should focus discovery and development efforts on agents that revolutionize how we potentiate antibiotics. To this end, there has been renewed interest in phage therapies, virulence inhibitors, bacterial growth rate modulators, monoclonal antibodies, and other approaches to augment antibiotic effects. Herein, we suggest that the unmet medical need is less about adding poorly-differentiated antibiotics to our armamentarium and more about the need for innovation in how we augment antibiotic regimen effects.